MODIFICATION OF TUBULARIZED INCISED PLATE URETHROPLASTY IN HYPOSPADIUS REPAIR FOR PREVENTING FISTULA AND MEATAL STENOSIS. - Mohammed., Ahmed; Hussein, Malath Anwar; Bresam, Mohammed (AL-Kindy College Medical Journal, 2013)
Objective: to evaluate the benefit of coverage of the urethral repair by dorsal dartos flap as a second layer for preventing fistula and V like incision on the tip of the glans for preventing meatal stenosis. Patients and Methods: Forty five children included in this study age ranged ( 11 months – 7 years), they underwent hypospadias repair between December 2008 to March 2012, all cases with distal hypospadias, same technique used for all patients, a combination of techniques used for reconstruction starting withtubularized incised plate urethroplasty with deepithelialized or stripping of the skin from both sides of U shaped incision surrounding the urethral plate, adding a V like incision on the top (tip of glans) of the midline urethral plate incision that give wide meatus subsequently prevent meatal stenosis and no need for dilatation after stent removal, followed by harvesting well vascularized dartos flap from de-epithelialized preputial skin and transposing itventrally by buttonholing maneuver and suturing the flap as a second layer along the neourthral suture line, finally approximation of glans , so achieving three layer closure. Results :All patients are followed for (6 months- 24 months) mean was 15 months, only two patients (4.4%) complicated with small fistula at the subcoronal region at the beginning of the study operated after 6 months and the fistula closed successfully. Twenty five cases (55.5%) with Chordee were completely released with no recurrence. No dilatation was needed after removal of stent for neomeatus developed a good stream of urine with no problems regarding stenosis. Conclusions: In this study hypospadias repair should achieve three layer closures by using a dartosfalp as a second layer to cover neourethral suture line combined with stripping the skin on the edge of the U shaped incision to gain secure closure of the neourethra, which will prevent fistula formation. We recommend adding a Vincision on the tip of the glans connected with midline urethral plate incision to prevent meatal stenosis.